A DNA/DMXAA/Metal–Organic Framework Activator of Innate Immunity for Boosting Anticancer Immunity. Issue 15 (6th March 2023) - Chen, Xiaojing; Tang, Qianyun; Wang, Jinqiang; Zhou, Yan; Li, Fengqin; Xie, Yuexia; Wang, Xingang; Du, Ling; Li, Junru; Pu, Jun; Hu, Quanyin; Gu, Zhen; et al.
Abstract: Immunotherapy has achieved revolutionary success in clinics, but it remains challenging for treating hepatocellular carcinoma (HCC) characterized by high vascularization. Here, it is reported that metal–organic framework‐801 (MOF‐801) can be employed as a stimulator of interferon genes (STING) through Toll‐like receptor 4 (TLR4) not just as a drug delivery carrier. Notably, cytosine–phosphate–guanine oligodeoxynucleotides (CpG ODNs) and 5, 6‐dimethylxanthenone‐4‐acetic acid (DMXAA) STING agonist with vascular disrupting function coordinates with MOF‐801 to self‐assemble into a nanoparticle (MOF‐CpG‐DMXAA) that effectively delivers CpG ODNs and DMXAA to cells for synergistically improving the tumor microenvironment by reprogramming tumor‐associated macrophages (TAMs), promoting dendritic cells (DCs) maturation, as well as destroying tumor blood vessels. In HCC‐bearing mouse models, it is demonstrated that MOF‐CpG‐DMXAA triggers systemic immune activation and stimulates robust tumoricidal immunity, resulting in a superior immunotherapeutic efficiency in orthotopic and recurrent HCC. Abstract : A multifunctional therapeutic immune‐nanomedicine, MOF‐CpG‐DMXAA, effectively delivers cytosine–phosphate–guanine oligodeoxynucleotides (CpG ODNs) and 5, 6‐dimethylxanthenone‐4‐acetic acid (DMXAA) to improve the miserable immune response by reprogramming tumor‐associated macrophages (TAMs), promoting dendritic cells (DCs) maturation and inhibiting angiogenesis, achieving synergistically immunotherapy. MOF‐CpG‐DMXAA significantly enhances stimulator of interferon genes (STING) activation, reverses the immunosuppression state and stimulates robust tumoricidal immunity, exhibiting a synergistic efficiency to eradicate hepatocellular carcinoma.